Studi Independen Kampus Merdeka and industry collaboration in developing graduate competencies - Neneng Halimatusadiah; Laksmi Dewi; Rusman Rusman (Himpunan Pengembang Kurikulum Indonesia, 2026)
Political interference in teacher recruitment has become a critical issue in the education sector because it can impact the quality and integrity of the education system. In many cases, the recruitment process is influenced by political interests, nepotism, and unfair selection practices, thus undermining the principle of meritocracy. This situation can lead to the selection of teachers who lack professional qualifications and competencies, ultimately impacting the quality of education and the effectiveness of the learning process. This study aims to analyze the forms of political interference in teacher recruitment and assess their impact on the quality of education. This study conducted a literature review, analyzing academic journals and prior research on political interference and teacher recruitment. The data obtained were analyzed descriptively through thematic analysis to identify key patterns and findings. The results show that political interference generally occurs through political pressure, manipulation of recruitment procedures, and bias toward certain candidates. These practices undermine teacher professionalism, reduce transparency in recruitment, and contribute to a decline in educational quality. This study concludes that a transparent, accountable, and merit-based recruitment system is crucial for minimizing political interference and improving the quality of education. Abstrak Ketenagakerjaan Indonesia mengarah pada peningkatan kebutuhan tenaga kerja terampil di berbagai sektor industri pasca pandemi COVID-19, sementara pendidikan abad ke-21 semakin menekankan kurikulum yang fleksibel dan personal serta kolaborasi erat antara perguruan tinggi dan masyarakat. Penelitian ini mengkaji bagaimana kebijakan Kampus Merdeka yang dikeluarkan oleh Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi mendukung kolaborasi antara perguruan tinggi dan industri dalam memperkuat kompetensi lulusan, dengan fokus khusus pada kegiatan Studi Independen. Penelitian ini menggunakan metode tinjauan literatur naratif dengan sintesis tematik terhadap artikel jurnal nasional dan internasional terindeks, prosiding, serta buku akademik yang terbit pada rentang 2019-2024. Tinjauan tersebut ditelaah, dikodekan, dan disintesis secara kritis berdasarkan tiga pertanyaan penelitian. Temuan menunjukkan bahwa integrasi yang kuat antara pendidikan tinggi dan industri memperkaya pengalaman belajar mahasiswa dan menyelaraskan kurikulum dengan praktik industri yang aktual, sehingga secara substansial meningkatkan relevansi pendidikan dengan pasar kerja yang dinamis dan kompetitif serta memperkuat keterampilan pemecahan masalah dan soft skills mahasiswa. Penelitian ini menyimpulkan bahwa pemanfaatan optimal kebijakan Kampus Merdeka memerlukan kolaborasi yang erat dan terkelola dengan baik antara perguruan tinggi dan industri untuk menghasilkan lulusan siap kerja yang mampu beradaptasi dengan perubahan pasar kerja yang cepat, sehingga meningkatkan daya serap lulusan di dunia kerja. Kata Kunci: kampus merdeka; kolaborasi industri; kompetensi; studi independen